Syndromic Craniosynostosis Can Define New Candidate Genes for Suture Development or Result from the Non-specifc Effects of Pleiotropic Genes: Rasopathies and Chromatinopathies as Examples - Zollino, Marcella; Lattante, Serena; Orteschi, Daniela; Frangella, Silvia; Doronzio, Paolo N.; Contaldo, Ilaria; Mercuri, Eugenio; Marangi, Giuseppe (Frontiers in Neuroscience, 2017)
Craniosynostosis is a heterogeneous condition caused by the premature fusion of cranial sutures, occurring mostly as an isolated anomaly. Pathogenesis of nonsyndromic forms of craniosynostosis is largely unknown. In about 15-30% of cases craniosynostosis occurs in association with other physical anomalies and it is referred to as syndromic craniosynostosis. Syndromic forms of craniosynostosis arise from mutations in genes belonging to the Fibroblast Growth Factor Receptor (FGFR) family and the interconnected molecular pathways in most cases. However it can occur in association with other gene variants and with a variety of chromosome abnormalities as well, usually in association with intellectual disability (ID) and additional physical anomalies. Evaluating the molecular properties of the genes undergoing intragenic mutations or copy number variations (CNVs) along with prevalence of craniosynostosis in different conditions and animal models if available, we made an attempt to define two distinct groups of unusual syndromic craniosynostosis, which can reflect direct effects of emerging new candidate genes with roles in suture homeostasis or a nonspecific phenotypic manifestation of pleiotropic genes, respectively. RASopathies and 9p23p22.3 deletions are reviewed as examples of conditions in the first group. In particular, we found that craniosynostosis is a relatively common component manifestation of cardio-facio-cutaneous (CFC) syndrome. Chromatinopathies and neurocristopathies are presented as examples of conditions in the second group. We observed that craniosynostosis is uncommon on average in these conditions. It was randomly associated with Kabuki, Koolen-de Vries/KANSL1 haploinsufficiency and Mowat-Wilson syndromes and in KAT6B-related disorders. As an exception, trigonocephaly in Bohring-Opitz syndrome reflects specific molecular properties of the chromatin modifier ASXL1 gene. Surveillance for craniosynostosis in syndromic forms of intellectual disability, as well as ascertainment of genomic copy number variations by array-CGH in apparently nonsyndromic craniosynostosis is recommended, to allow for improvement of both the clinical outcome of patients and the accurate individual diagnosis.